PERANCANGAN SISTEM INFORMASI PEMETAAN WILAYAH AIR BAKU KOTA TASIKMALAYA (SIPWARKOT) PADA UPTD PSDA WILAYAH SUNGAI CIWULAN-CILAKI - Yani Sri Mulyani; Tuti Alawiyah; Muhamad Rivalda (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2023)
Geographic information systems or GIS are information systems related to geographical features and are used to manipulate and display information in a geographical area. GIS can also be used for mapping, particularly in raw water areas. At the UPTD PSDA Ciwulan-Cilaki River Area, there are problems in managing data on applications for the submission of raw water requests carried out by the community. The applicant was required to send a letter requesting the submission of raw water to the agency, which resulted in the piling up of letters in the archives. Another problem found is that the survey process feels very long and takes days. This aimed of this researched was to design a geographic information system to solve the problem. In this research, the researchers designed a geographic information system mapping the raw water area of Tasikmalaya City based on Android using the Prototype method. The stages in the Prototype method are Communication, Planning, Representation, and Construction. The benefits and results of this information system design were that it made it easier for applicants to apply for raw water along with mapping the raw water area and for application management agencies to be more structured. In addition, this android-based GIS could be accessed by applicants and agencies anytime and anywhere.